The role of higher education in promoting lifelong learning (Lifelong learning policies and strategies, 2015)
This new UIL publication reports on how higher education institutes (HEIs) face a strategic imperative to broaden access to lifelong learning opportunities and ensure that education and learning are available to a diverse student population. Given the on-going process of globalization, demographic shifts in many countries, and the rapid pace of technological advancement, this book, the third volume in UIL's series on Lifelong Learning Policies and Strategies, discusses various ways that higher education can promote life¬long learning, paying due consideration to regional disparities and specificities. These include responses to the learning needs of older adults in China, the challenge of implementing recurrent education in Japan, European efforts to develop a common approach to lifelong learning at university, and how a lifelong learning approach is put into practice in higher education in Australia